The effect of controlling the distance and height of the board in the development of some cognitive abilities (sense-kinetic) and Learnning of the accuracy of the correction skill of stability (free throw) basketball - Dr. Ali Fattah M. Omar Mohammed (physical education and sport sciences college for women/ Baghdad University, 2020)
The aim of the current research is to identify the effect of board height control on developing perception (sense-kinetics) and developing the accuracy of correction skill from consistency and accuracy to fifth-grade primary students. The researchers used the experimental method for its appropriateness and the nature of the research. The research community consists of students from Al-Dhiyaa Elementary School for Boys for the academic year (2018/2019). (B) (22), (c) number (21), (d) number (25), and by lot Division (B) was chosen to be the first experimental group that uses the control method for the correction area distance, and Division A to be the second experimental group that uses the board height control method, and Division (C) to be the third experimental group that uses the control method for correction and board height. And Division (D) to be the control group that uses the method followed by the teacher. At the rate of (10) students per group, the data were statistically treated using the  statistical bag (Spss).  The researchers concluded the following: - The gradient with high board showed a remarkable superiority between the pre and post tests and in favor of the post test of the second experimental group.